INNOVATIVE STRATEGIES IN THE USE OF VITAMIN E AND ROSEMARY AS ANTIMICROBIAL AGENTS FOR ENHANCING THE SAFETY AND PRESERVATION OF MINCED POULTRY MEAT DURING REFRIGERATION - S. M. Farhan; H. M. Alnori; S. I. Yousif; N. Mirzan; S. Abdulateef; N. M. Jebril; A. A. Al-Azzami; O. A. Saeed; B. F. Sulaiman; S. Y. Sardary (مجلة الأنبار للعلوم الزراعية)
This study evaluated the bactericidal efficacy of vitamin E and rosemary extracts in minced poultry meat stored at a refrigeration temperature of 4° C. Six distinct interventions were assessed: a control group (Group 1), three treatments involving thighs from broilers supplemented with vitamin E (300 mg/kg) (Group 2), and thighs from broilers fed rosemary leaf powder at two levels of 0.5% and 1%/kg (Groups 3 and 4). Groups 5 and 6 utilized thighs from the control group that were sprayed with 0.5%/kg of aqueous and alcoholic rosemary extracts, respectively. The study showed that incorporating rosemary and vitamin E extracts into minced chicken significantly reduced colony-forming units (CFU) of total bacteria, E. coli, and psychrophilic bacteria relative to the control group. The alcoholic rosemary extract exhibited the most significant reduction in bacterial counts, followed closely by the aqueous rosemary extract and rosemary leaf powder at the 1%/kg dosage. There were no significant differences in reductions in E. coli and psychrophilic bacteria between the vitamin E therapy and the control group. The findings indicate that rosemary extracts, especially in alcoholic form, function as potent antibacterial agents that preserve the quality of minced fowl during storage, potentially extending shelf life and reducing spoilage. Research suggests that utilizing natural preservatives like rosemary and vitamin E may effectively replace synthetic compounds in scenarios where maintaining consistent refrigeration is challenging. Natural preservatives can improve the safety and quality of meat products, and in meeting consumer demand for healthier and more sustainable food options